Pharmacogenomics: an opportunity for safer and efficient pharmacotherapy (Research, Society and Development, 2022)
Responses to drugs are influenced by multiple factors, including health status, environmental influences, and genetic characteristics. The bioavailability of a drug can vary widely among individuals with a similar weight under the same drug dosage, which might result in toxicity and adverse drug reactions (ADRs). Genetic polymorphisms are known causes of interindividual differences in disease risk and treatment response in humans. In fact, a relevant number of associations between human genetic variants and predisposition to adverse events were described for diverse kinds of drug interactions, involving hundreds of proteins like receptors, transporters, and metabolizing enzymes. In this way, Pharmacogenetics and Pharmacogenomics emerged aiming to determine the genetic component responsible for drug response. A particular attention is showed if a treatment benefits (or harms) a particular subgroup, considering the interaction between treatment and genetic background. In this scenario, researchers have focused on better understanding personalized medicine, which holds the potential to maximize drug efficiency and minimize toxic effects. This review aims to introduce some principles, perspectives, and clinical applications of pharmacogenetics, emphasizing important findings and clinical applications that may contribute to therapeutical improvement.